MYOFASCIAL PAIN SYNDROME - Shahdevi Nandar Kurniawan; Nidia Suriani; Eko Arisetijono Marhaendraputro; Dessika Rahmawati (Journal of Pain, Headache and Vertigo, 2020)
Pain is a sensory experience that is responded to as an unpleasant stimulus that is often caused by tissue damage. Perdossi defines pain as an unpleasant sensory and emotional experience due to tissue damage, both actual and potential, or which is described in the form of such damage. Pain can affect everyone regardless of sex, age, race, social status, and occupation. Myofascial pain syndrome (MPS) is a term used to describe the condition of acute or chronic pain in musculoskeletal soft tissue. This is indicated by the findings of sensory, motoric, and autonomic symptoms related to myofascial trigger points (MTRP). The symptoms can be local or far from MTRP. In MPS that are far from MTRP, the pain patterns that appear are usually pain is pervasive The most common location for MPS is the neck and back. The purpose of writing this literature review is to explain epidemiology, clinical manifestations, pathogenesis mechanisms, pathophysiology mechanisms, and management in patients with myofascial pain syndrome. Myofascial pain syndrome is a pain syndrome in muscles that includes musculoskeletal abnormalities and MPS management shows that most interventions, both medical therapy and non-medical therapy, still need studies to prove its effectiveness.